Mortality from Breast Cancer in Women under 50 Years of Age in Colombia - González Mariño, Mario Arturo (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To calculate and analyze the mortality rates from breast cancer in women under 50 years of age in Colombia and to compare them with those of other countries in the region.Methods Based on data from the registry of deaths in 2018 and the results of the National Population and Housing Census of Colombia for the same year, specific mortality rates in women with breast cancer, specific mortality according to age group, standardized by age, proportional mortality, potential years of life lost, and years of life expectancy lost in women under 50 years of age who died from breast cancer were calculated. The mortality rate of regional countries was consulted on the Global Cancer Observatory webpage.Results In the group from 20 to 49 years, the specific mortality rate was higher in the age range from 45 to 49 years, with a rate of 23.42 × 100,000, a value that was above the specific mortality rate due to breast cancer in women in Colombia, 15.17 × 100.000. In the age range of 45 to 49 years, the potential years of life lost were 42.16. Of the 0.275 years of life expectancy lost by the population due to this neoplasia, women under 50 years of age represented 0.091 (33%). Colombia is the fifth in the rank of mortality in Latin American countries in this age group.Conclusion Breast cancer in patients from 30 to 59 years is the number one cause for the decrease in life expectancy of women in Colombia. Women under 50 years of age represent one third of this decrease. This neoplasm is also the leading cause of mortality in women younger than 50 years in South America.
Keywords: neoplasms; breast; mortality; women; demography; Colombia; South America